Building Teacher Independence in Teaching Physical Education and Sports through Community Service Programs: Towards Effective and Enjoyable Learning - Noer Fadlan, Muhammad; Friska, Novita; Ansor, Arrini Shabrina; Landong, Ahmad (Journal of Community Service For Indonesian Society, 2023)
This article documents the community service program implemented in Tembung Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, with a focus on developing physical education and sports in elementary schools. This program is designed to address some of the main challenges faced by teachers in the region, such as limited human resources, lack of knowledge about innovative teaching methods, and a lack of curriculum that is integrated with students' physical health and well-being. Through a series of training activities, development of sports facilities, and active collaboration between the foundation, local government and community, this program has succeeded in achieving various significant results and outcomes. This article details the implementation methods, results achieved, as well as plans for the next stages of the program, including efforts to involve the community more actively, development of extracurricular programs, further training for teachers, and development of more complete sports facilities. This article also highlights the main conclusions of the program, important suggestions for continuing the program, and references used in developing the program and writing this article.